Optical laminate, method for producing same, and smart window including same
By eliminating the need for a separate substrate and forming the conductive layer directly on the polarizing plate, the variable transmittance optical laminate addresses the challenges of increased costs, thickness, and transmittance issues in conventional laminates, achieving improved reliability, performance, and appearance.
Patent Information
- Application Number
- JP2024549542
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-22
- Filing Date
- 2023-01-02
- Publication Date
- 2025-03-21
AI Technical Summary
Conventional variable transmittance optical laminates require a separate substrate for forming the conductive layer, leading to increased manufacturing costs, thicker laminates, and transmittance issues due to phase differences. Additionally, the absence of a separate substrate can result in cracks and chemical reactions during the bonding process, affecting the reliability and appearance of the laminate.
The variable transmittance optical laminate eliminates the need for a separate substrate by forming the conductive layer directly on one surface of the polarizing plate. This design simplifies the manufacturing process, reduces thickness, and improves transmittance in the light-transmitting mode. It also incorporates a functional layer to enhance surface hardness, minimize cracks, and optimize the number and distribution of ball spacers within the liquid crystal layer.
This approach results in a thinner, more reliable, and cost-effective variable transmittance optical laminate with improved transmittance and surface hardness. The simplified manufacturing process reduces the risk of cracks and chemical reactions, leading to enhanced performance and appearance.
Smart Images

Figure 2025507633000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a variable transmittance optical laminate, a method for producing the same, and a smart window including the same. [Background technology]
[0002] In general, an external light blocking coating is often applied to glass windows of vehicles and other means of transportation. However, the glass windows of conventional means of transportation have a fixed transmittance, and the external light blocking coating also has a fixed transmittance. Therefore, the windows of such conventional means of transportation have a fixed overall transmittance, which may lead to accidents. For example, if the overall transmittance is set low, there is no problem during the day when there is sufficient light in the surroundings, but there is a problem that the driver, etc. has difficulty in properly checking the surroundings of the means of transportation at night when there is insufficient light in the surroundings. Alternatively, if the overall transmittance is set high, there is a problem that the driver, etc. may be dazzled during the day when there is sufficient light in the surroundings. For this reason, a variable transmittance optical laminate capable of changing the transmittance of light when a voltage is applied has been developed.
[0003] The variable transmittance optical stack is driven by applying a voltage to drive the liquid crystal to change the transmittance. The variable transmittance optical stack developed to date is manufactured by forming a conductive layer for driving the liquid crystal on a separate substrate and combining it with other elements such as a polarizer.
[0004] For example, Japanese Patent Application Laid-Open No. 2018-010035 also discloses a variable transmittance optical laminate including a transparent electrode layer formed on a polycarbonate (PC) substrate having a predetermined thickness.
[0005] However, when a separate substrate is used to form the conductive layer, the manufacturing process becomes complicated, which increases manufacturing costs, and the thickness of the laminate increases, resulting in a phase difference and causing a change in transmittance.
[0006] In addition, if a separate substrate for forming a conductive layer is not included to solve the above problem, cracks may occur in components such as the conductive layer due to pressure applied by the spacer during the process, especially during the bonding process of the upper and lower plates, and chemical reactions between the liquid crystal and the alignment film.
[0007] Furthermore, in the case of some conventional optical laminates, there are problems such as a decrease in transmittance or haze due to the spacer, or unevenness is visible, resulting in poor liquid crystal appearance or a decrease in spacer reliability.
[0008] Therefore, there is a need to develop a variable transmittance optical laminate that does not include a separate substrate for forming a conductive layer, thereby simplifying the manufacturing process and reducing the thickness, while preventing cracks or scratches that may occur during the process, improving the reliability of the spacer, and improving the appearance of the liquid crystal. Summary of the Invention [Problem to be solved by the invention]
[0009] An object of the present invention is to provide a variable transmittance optical laminate that does not require a separate substrate for forming a conductive layer, and thus has a simplified manufacturing process.
[0010] Another object of the present invention is to provide a variable transmittance optical laminate that does not include a separate substrate for forming a conductive layer, and thus has a significantly reduced thickness.
[0011] Another object of the present invention is to provide a variable transmittance optical laminate having improved transmittance in a transmission mode by not including a separate substrate for forming a conductive layer.
[0012] Another object of the present invention is to provide a variable transmittance optical laminate that includes a functional layer that can improve surface hardness, thereby minimizing cracks or scratches that occur during processing.
[0013] Another object of the present invention is to provide a variable transmittance optical laminate that can suppress appearance defects that may occur in the liquid crystal layer by providing an optimal range of ball spacers contained in the liquid crystal layer.
[0014] Another object of the present invention is to provide a variable transmittance optical laminate in which a ball spacer contained in a liquid crystal layer is provided via an adhesion imparting layer, thereby further improving the reliability of the spacer.
[0015] Another object of the present invention is to provide a smart window including the variable transmittance optical laminate, and a means of transportation, a wearable device, or a building fixture to which the smart window is applied.
[0016] However, the problems to be solved by the present invention are not limited to those mentioned above, and other problems not mentioned will be clearly understood by those skilled in the art from the following description. [Means for solving the problem]
[0017] The present invention includes a first laminate in which a first polarizing plate including a first functional coating layer, a first transparent conductive layer, and a first alignment film are laminated in this order; a second laminate facing the first laminate in which a second polarizing plate including a second functional coating layer, a second transparent conductive layer, and a second alignment film are laminated in this order; and a liquid crystal layer disposed between the first laminate and the second laminate, the liquid crystal layer including a ball spacer provided via an adhesion imparting layer formed on at least one of the first alignment film and the second alignment film, the ball spacer having a diameter of 4 to 10 μm, at least one of the first transparent conductive layer and the second transparent conductive layer being formed in direct contact with at least one of the first polarizing plate and the second polarizing plate, the first functional coating layer and the second functional coating layer each having a Vickers Hardness (HV) of 18 to 41, and the ball spacer The diameter (d; μm) of the spacer relative to the unit area (1 mm 2 The number of ball spacers (A) per 100 .mu.m is for a variable transmittance optical stack that satisfies Equation 1 below. [Formula 1] -1.3333d 3 +32.321d 2 -265.2d+802.14≦A≦-17.639d 3 +427.26d 2 -3502.2d+10736
[0018] In a first aspect, the present invention provides a ball spacer having a diameter (d; μm) per unit area (1 mm 2 The number of ball spacers (A) per i) When 4≦d<4.5, A is 184 to 2,420, ii) 4.5≦d<5.5, A is 118 to 1,550, iii) 5.5≦d<6.5, A is 98 to 1,290, iv) When 6.5≦d<7.5, A is 84 to 1,105, v) When 7.5≦d<8.5, A is 74 to 970; vi) When 8.5≦d<9.5, A is 65 to 860; vii) When 9.5≦d≦10, A may satisfy the relationship 59 to 775.
[0019] In a second aspect, the present invention provides a ball spacer having a diameter (d; μm) per unit area (1 mm 2 The number of ball spacers per ball spacer (A) and the Vickers hardness (B) of the functional coating layer are i) When 4≦d<4.5, A×B 2 60,000 to 1,650,000, ii) When 4.5≦d<5.5, A×B 2 40,000 to 1,050,000, iii) When 5.5≦d<6.5, A×B 2 31,000 to 900,000, iv) 6.5≦d<7.5, A×B 2 27,000 to 800,000, v) When 7.5≦d<8.5, A×B 2 24,000 to 700,000, vi) When 8.5≦d<9.5, A×B 2 21,000 to 600,000, vii) When 9.5≦d≦10, A×B 2 may satisfy the relationship between 19,000 and 550,000.
[0020] In the third aspect of the present invention, the adhesion imparting layer may be formed integrally with a ball spacer.
[0021] In a fourth aspect of the present invention, an area of the ball spacer in the liquid crystal layer may be 0.01% to 10% of an area of the liquid crystal layer.
[0022] In a fifth aspect of the present invention, the first functional coating layer and the second functional coating layer may each include at least one of a hard coating layer and a low refractive index layer.
[0023] In a sixth aspect of the present invention, the low refractive index layer may contain one or more selected from the group consisting of SiO2, Al2O3, MgF2, CaF2 and cryolite.
[0024] In a seventh aspect of the present invention, at least one of the first transparent conductive layer and the second transparent conductive layer may be formed in direct contact with either one of the first polarizing plate and the second polarizing plate without the inclusion of a separate substrate between the transparent conductive layer and either one of the first polarizing plate and the second polarizing plate.
[0025] In an eighth aspect of the present invention, at least one of the first transparent conductive layer and the second transparent conductive layer may include an easy-adhesion layer between the transparent conductive layer and one of the first polarizing plate and the second polarizing plate, and may be formed in direct contact with the transparent conductive layer.
[0026] In a ninth aspect of the present invention, at least one of the first transparent conductive layer and the second transparent conductive layer may contain one or more materials selected from the group consisting of transparent conductive oxides, metals, carbon-based materials, conductive polymers, conductive inks, and nanowires.
[0027] In a tenth aspect of the present invention, at least one of the first polarizing plate and the second polarizing plate may further include one or more layers selected from the group consisting of a protective layer, a phase difference adjusting layer, and a refractive index adjusting layer.
[0028] In an eleventh aspect of the present invention, at least one of the first polarizing plate and the second polarizing plate may have a thickness of 30 to 200 μm.
[0029] In a twelfth aspect of the present invention, the variable transmittance optical laminate may further include one or more layers selected from the group consisting of an overcoat layer, an adhesive layer, and an ultraviolet absorbing layer.
[0030] The present invention also relates to a method for producing the variable transmittance optical laminate.
[0031] The present invention also relates to a smart window including the variable transmittance optical laminate.
[0032] The present invention also relates to a means of transportation comprising said smart window.
[0033] The present invention also relates to an automobile in which the smart window is applied to at least one of a front window, a rear window, a side window, a sunroof window, and an interior partition.
[0034] The present invention also relates to a wearable device including the smart window.
[0035] The present invention also relates to a building fixture including the smart window. Effect of the Invention
[0036] According to the variable transmittance optical laminate of the present invention, the process of forming a conductive layer on a substrate and then bonding it to other components required for forming a conventional optical laminate can be omitted, and the manufacturing process can be simplified compared to the conventional optical laminate.
[0037] In addition, according to the variable transmittance optical laminate of the present invention, a conductive layer is formed directly on one side of a polarizing plate, and a separate substrate for forming the conductive layer is not required, so that the thickness can be significantly reduced compared to conventional optical laminates.
[0038] In addition, according to the variable transmittance optical laminate of the present invention, a conductive layer is formed directly on one side of a polarizing plate, and a separate substrate for forming the conductive layer is not included, so that the transmittance in the light transmission mode can be improved compared to conventional optical laminates.
[0039] In addition, the variable transmittance optical laminate according to the present invention includes a functional layer capable of improving surface hardness, thereby minimizing cracks or scratches that occur during processing compared to conventional optical laminates.
[0040] In addition, according to the variable transmittance optical laminate of the present invention, the ball spacers provided in the liquid crystal layer are included in an optimal number range, so that the occurrence of appearance defects that may occur in the liquid crystal layer can be significantly reduced compared to conventional optical laminates.
[0041] In addition, according to the variable transmittance optical laminate of the present invention, the ball spacer included in the liquid crystal layer is provided on the alignment film via an adhesion imparting layer, so that the reliability of the spacer can be further improved compared to conventional optical laminates. [Brief description of the drawings]
[0042] [Figure 1] FIG. 1 is a diagram showing a layered structure of a variable transmittance optical layered body according to an embodiment of the present invention. [Figure 2a] FIG. 2a is an enlarged view of region M in FIG. [Figure 2b] FIG. 2b is an enlarged view of region M in FIG. [Figure 2c] FIG. 2c is an enlarged view of region M in FIG. [Figure 3a] FIG. 3a is a diagram showing a laminate structure of a polarizing plate according to an embodiment of the present invention. [Figure 3b] FIG. 3b is a diagram showing a laminate structure of a polarizing plate according to an embodiment of the present invention. [Figure 3c] FIG. 3c is a diagram showing a laminate structure of a polarizing plate according to an embodiment of the present invention. [Figure 4] FIG. 4 is a diagram showing a layered structure of a variable transmittance optical layered body according to another embodiment of the present invention. [Diagram 5] FIG. 5 is a diagram showing a layered structure of a smart window according to an embodiment of the present invention. [Figure 6a] FIG. 6a is a diagram showing a laminated structure of a smart window according to one embodiment of the present invention. [Figure 6b] FIG. 6b is a diagram showing a laminated structure of a smart window according to one embodiment of the present invention. [Figure 7] FIG. 7 is an image showing the occurrence of black amorphous unevenness. [Figure 8] FIG. 8 is an image showing the occurrence of white dot-shaped irregularities. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0043] The present invention relates to a variable transmittance optical laminate in which a conductive layer for driving liquid crystal is directly formed on one side of a polarizing plate, which does not include a separate substrate for forming the conductive layer, thereby reducing the thickness of the laminate, the transmittance in a light transmission mode is improved, cracks or scratches generated during the process can be minimized by including a functional layer that can improve surface hardness, and the number range of ball spacers included in the liquid crystal layer is appropriately controlled to reduce the occurrence of defects in the appearance of the liquid crystal layer, and in particular, the ball spacers are provided on an alignment film via an adhesion imparting layer, thereby improving the reliability of the spacers.
[0044] More specifically, the liquid crystal display device includes a first laminate including a first polarizing plate including a first functional coating layer, a first transparent conductive layer, and a first alignment film laminated in this order, a second laminate facing the first laminate including a second functional coating layer, a second transparent conductive layer, and a second alignment film laminated in this order, and a liquid crystal layer disposed between the first laminate and the second laminate, the liquid crystal layer including a ball spacer provided via an adhesion imparting layer formed on at least one of the first alignment film and the second alignment film, the ball spacer having a diameter of 4 to 10 μm, at least one of the first transparent conductive layer and the second transparent conductive layer being formed in direct contact with at least one of the first polarizing plate and the second polarizing plate, the first functional coating layer and the second functional coating layer each having a Vickers Hardness of 18 to 41, and the ball spacer The diameter (d; μm) of the spacer relative to the unit area (1 mm 2 The number of ball spacers (A) per 100 .mu.m is for a variable transmittance optical stack that satisfies Equation 1 below. [Formula 1] -1.3333d 3 +32.321d 2 -265.2d+802.14≦A≦-17.639d 3 +427.26d 2 -3502.2d+10736
[0045] The variable transmittance optical laminate of the present invention is particularly suitable for technical fields in which light transmittance can be changed by applying a voltage, and can be used, for example, in smart windows.
[0046] A smart window is an optical structure that controls the amount of light or heat passing through by changing the light transmittance according to the application of an electric signal. That is, a smart window is designed to be able to change to a transparent, opaque or translucent state according to a voltage, and is also called variable transmittance glass, light control glass or smart glass.
[0047] The smart window may be used as a partition for dividing or protecting privacy in the interior space of a vehicle or building, or as a light window placed in an opening of a building, or as a highway sign, bulletin board, odometer, clock, or advertising screen, and may be used to replace glass in vehicles such as windows or sunroofs of automobiles, buses, airplanes, ships, or trains.
[0048] The variable transmittance optical laminate of the present invention can also be used in smart windows in the various technical fields described above, but since the conductive layer is directly formed on the polarizing plate, no separate substrate is required for forming the conductive layer, and therefore the thickness is thin and the bending characteristics are advantageous, and the variable transmittance optical laminate of the present invention can be particularly suitably used in smart windows for vehicles or buildings. In one or more embodiments, the smart window to which the variable transmittance optical laminate of the present invention is applied can be used in transportation, for example, front windows, rear windows, side windows, and sunroof windows of automobiles, or building fixtures, and can be used for dividing the interior space of automobiles or buildings, such as interior partitions, or for privacy protection, in addition to blocking external light, and can also be used in wearable devices such as helmets, glasses, or watches.
[0049] Hereinafter, the embodiments of the present invention will be described in more detail with reference to the drawings. However, the following drawings attached to this specification are intended to illustrate preferred embodiments of the present invention and to facilitate a better understanding of the technical concept of the present invention together with the above-mentioned content of the invention, and therefore the present invention should not be interpreted as being limited only to the matters described in these drawings.
[0050] The terms used herein are for the purpose of describing the embodiments and are not intended to limit the present invention. In the present specification, the singular form includes the plural form unless otherwise specified in the phrase. For example, the term "polarizer" used herein may mean at least one polarizer of the first polarizer and the second polarizer, the term "transparent conductive layer" may mean at least one transparent conductive layer of the first transparent conductive layer and the second transparent conductive layer, the term "functional coating layer" may mean at least one functional coating layer of the first functional coating layer and the second functional coating layer, and the term "alignment film" may mean at least one alignment film of the first alignment film and the second alignment film.
[0051] As used herein, the terms "comprises" and / or "comprising" are used in a sense that does not exclude the presence or addition of one or more other components, steps, operations and / or elements other than the stated components, steps, operations and / or elements. The same reference numerals refer to the same components throughout the specification.
[0052] Spatially relative terms such as "below," "bottom," "lower," "upper," "top," and the like, may be used to easily describe the relationship of one element or component to another element or component as depicted in the drawings. Spatially relative terms should be understood to include different orientations of elements in use or operation in addition to the orientation depicted in the drawings. For example, if an element depicted in the drawings is turned upside down, an element described as "below" or "below" another element may be placed "above" the other element. Thus, the exemplary term "below" can include both an orientation of below and above. Elements may be oriented in other directions, and thus the spatially relative terms may be interpreted accordingly.
[0053] As used herein, the "planar direction" can be interpreted as the direction perpendicular to the polarizer and / or transparent conductive layer, ie, the direction viewed from the user's viewing side.
[0054] As used in this specification, "substantially" can be interpreted to include not only being completely identical or identical physically, but also being within the range of error in measurement or manufacturing processes, for example, an error range of 0.1% or less.
[0055] Figure 1 is a diagram showing the laminate structure of a variable transmittance optical laminate for one embodiment of the present invention, Figure 2 is an enlarged diagram of area M in Figure 1, Figure 3 is a diagram showing the laminate structure of a polarizing plate for one or more embodiments of the present invention, Figure 4 is a diagram showing the laminate structure of a variable transmittance optical laminate for another embodiment of the present invention, Figures 5 and 6 are diagrams showing the laminate structure of a smart window for one or more embodiments of the present invention, Figure 7 is an image showing the occurrence of black amorphous unevenness, and Figure 8 is an image showing the occurrence of white dot-shaped unevenness.
[0056] Referring to FIG. 1, a variable transmittance optical stack according to one embodiment of the present invention may include a first polarizer 100-1, a second polarizer 100-2, a first transparent conductive layer 200-1, a second transparent conductive layer 200-2, and a liquid crystal layer 300.
[0057] The polarizing plate 100 includes a polarizer 110 and at least one functional coating layer 120 for improving the surface hardness of the polarizing plate, and in one or more embodiments, may further include one or more layers selected from the group consisting of a protective layer 130, a phase difference adjustment layer 140, and a refractive index adjustment layer 150 (see FIG. 3).
[0058] The polarizer 110 may be any conventional or later developed polarizer, such as a stretched type polarizer or a coated type polarizer.
[0059] In one embodiment, the stretched polarizer may include a stretched polyvinyl alcohol (PVA)-based resin. The polyvinyl alcohol (PVA)-based resin may be a polyvinyl alcohol-based resin obtained by saponifying a polyvinyl acetate-based resin. Examples of polyvinyl acetate-based resins include polyvinyl acetate, which is a homopolymer of vinyl acetate, and copolymers of vinyl acetate and other monomers copolymerizable therewith. The other monomers may be unsaturated carboxylic acid-based, unsaturated sulfonic acid-based, olefin-based, vinyl ether-based, and acrylamide-based monomers having an ammonium group. The polyvinyl alcohol (PVA)-based resin may be modified, and may be, for example, polyvinyl formal or polyvinyl acetal modified with aldehydes.
[0060] In an embodiment, the coating type polarizer may be formed by a liquid crystal coating composition, which may include a reactive liquid crystal compound and a dichroic dye.
[0061] The reactive liquid crystal compound may refer to a compound that includes, for example, a mesogen skeleton and further includes one or more polymerizable functional groups. Such reactive liquid crystal compounds are variously known under the name of RM (Reactive Mesogen). The reactive liquid crystal compound can be polymerized by light or heat to form a cured film in which a polymer network is formed while maintaining the liquid crystal alignment.
[0062] The reactive liquid crystal compound may be a monofunctional or polyfunctional reactive liquid crystal compound. The monofunctional reactive liquid crystal compound is a compound having one polymerizable functional group, and the polyfunctional reactive liquid crystal compound is a compound having two or more polymerizable functional groups.
[0063] The dichroic dye is a component contained in the liquid crystal coating composition that imparts polarization properties and has a property that the absorbance in the long axis direction of the molecule is different from that in the short axis direction. The dichroic dye may be a dichroic dye that has been used or will be developed in the future, and may include at least one dye selected from the group consisting of azo dyes, anthraquinone dyes, perylene dyes, merocyanine dyes, azomethine dyes, phthaloperylene dyes, indigo dyes, dioxazine dyes, polythiophene dyes, and phenoxazine dyes.
[0064] The liquid crystal coating composition may further include a solvent capable of dissolving the reactive liquid crystal compound and the dichroic dye, such as propylene glycol monomethyl ether acetate (PGMEA), methyl ethyl ketone (MEK), xylene, chloroform, etc. The liquid crystal coating composition may further include a leveling agent, a polymerization initiator, etc., within a range that does not impair the polarization properties of the coating film.
[0065] The functional coating layer 120 is provided to improve the hardness of the polarizing plate 100, and is not particularly limited as long as it can improve the hardness of the polarizing plate, and may include, for example, a hard coating layer and / or a low refractive index layer.
[0066] The hard coating layer may be a conventional or later developed hard coating layer, and may be formed from a composition for forming a hard coating layer, including, for example, an acrylate or epoxy compound, inorganic fine particles, and / or a photoinitiator. The acrylate compound may include a monomer or oligomer containing a (meth)acrylate group, and the term "(meth)acryl-" as used herein is used to mean "methacryl-", "acryl-", or both. Non-limiting examples of the acrylate compound include neopentyl glycol acrylate, 1,6-hexanediol (meth)acrylate, propylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, 1,2,4-cyclohexane tetra(meth)acrylate, pentaglycerol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, and dipentaerythritol tri(meth)acrylate. Examples of the acrylates include 2-hydroxyethyl isocyanurate, dipentaerythritol penta(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol tri(meth)acrylate, tripentaerythritol hexatri(meth)acrylate, bis(2-hydroxyethyl)isocyanurate di(meth)acrylate, hydroxyethyl(meth)acrylate, hydroxypropyl(meth)acrylate, hydroxybutyl(meth)acrylate, isooctyl(meth)acrylate, iso-dexyl(meth)acrylate, stearyl(meth)acrylate, tetrahydrofurfuryl(meth)acrylate, phenoxyethyl(meth)acrylate, and isoborneol(meth)acrylate. These may be used alone or in combination of two or more.The acrylate compound may include an epoxy (meth)acrylate compound and / or a urethane (meth)acrylate compound. The epoxy compound may include a monomer or oligomer having at least one epoxy group in the molecule. The epoxy group may be an alicyclic epoxy group. The alicyclic ring included in the epoxy group may have 3 to 7 carbon atoms, for example, an alicyclic epoxy group (cyclohexyl epoxy) containing a cyclohexane ring. The alicyclic ring may have a substituent. For example, the alicyclic ring may include an alkyl substituent having 1 to 20 carbon atoms. If the alkyl substituent has more than 20 carbon atoms, it may be disadvantageous in terms of curing speed. The alkyl substituent may be a straight-chain type or a branched type, and if it is a branched type, the number of carbon atoms may be 3 or more.
[0067] According to an embodiment of the present invention, the composition for forming a hard coating layer includes inorganic fine particles. According to an embodiment of the present invention, the inorganic fine particles may be inorganic fine particles having a nano-scale particle size, for example, nano-particles having a particle size of 100 nm or less, or 10 to 100 nm, or 10 to 50 nm. Furthermore, the inorganic fine particles may be, for example, silica fine particles, aluminum oxide particles, titanium oxide particles, or zinc oxide particles. By including the inorganic fine particles, the hardness of the hard coating layer can be further improved. According to an embodiment of the present invention, the inorganic fine particles may be included in an amount of 10 to 60 parts by weight, or 20 to 50 parts by weight, based on 100 parts by weight of the composition for forming a hard coating layer. By including the inorganic fine particles in the above range, the hardness of the hard coating layer can be improved by adding the inorganic fine particles within a range that does not deteriorate the physical properties of the composition for forming a hard coating layer.
[0068] According to an embodiment of the present invention, the composition for forming a hard coating layer includes a photoinitiator, which may be, but is not limited to, 1-hydroxy-cyclohexyl-phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone, methylbenzoyl formate, α,α-dimethoxy-α-phenylacetophenone, 2-benzoyl-2-(dimethylamino-)-1-[4-(4-morpholinyl)phenyl]-1-butanone, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone diphenyl(2,4,6-trimethylbenzoyl)-phosphine oxide, or bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide. In addition, examples of products currently available on the market include Irgacure 184, Irgacure 500, Irgacure 651, Irgacure 369, Irgacure 907, Darocur 1173, Darocur MBF, Irgacure 819, Darocur TPO, Irgacure 907, Esacure KIP 100F, etc. These photoinitiators may be used alone or in combination of two or more different types.
[0069] According to an embodiment of the present invention, the photoinitiator may be included in an amount of 0.5 to 10 parts by weight, preferably 1 to 5 parts by weight, based on 100 parts by weight of the composition for forming a hard coating layer. When the photoinitiator is in the above range, sufficient crosslinking photopolymerization can be achieved without deteriorating the physical properties of the hard coating layer.
[0070] Meanwhile, the composition for forming a hard coating layer may further include additives commonly used in the technical field to which the present invention belongs, such as a surfactant, an anti-yellowing agent, a leveling agent, an antifouling agent, etc. In addition, the content of the additives is not particularly limited since it can be variously adjusted within a range that does not deteriorate the physical properties of the composition for forming a hard coating layer according to the present invention.
[0071] The low refractive index layer may be provided to improve the hardness of the polarizing plate within the scope of the present invention. The low refractive index layer may contain one or more low refractive index agents selected from the group consisting of SiO2, Al2O3, MgF2, CaF, and cryloite, and in some embodiments, may contain the compound or resin used in the hard coating layer. The hard coating layer and the low refractive index layer may be used alone, or in some embodiments, may be used as a multi-layer structure.
[0072] The functional coating layer 120 may be formed in direct contact with one surface of the polarizer 110 as shown in Figures 1 and 3a, but is not limited thereto. For example, when the polarizer includes the phase difference control layer 140 to the refractive index control layer 150, the functional coating layer 120 may be formed on one surface of the phase difference control layer 140 to the refractive index control layer 150, and the functional coating layer 120, the phase difference control layer 140 to the refractive index control layer 150, and the polarizer 110 may be sequentially laminated (see Figures 3b to 3c).
[0073] The functional coating layer 120 is preferably formed on the liquid crystal layer 300 side of the polarizer 110, i.e., on the inner side of the polarizer 110, and for example, the first functional coating layer 120-1 and the second functional coating layer 120-2 may be provided on the inner sides of the first polarizer 110-1 and the second polarizer 110-2, respectively, and disposed to face each other. In this case, the functional coating layer has an advantage of imparting a hardness level suitable for forming members such as a transparent conductive layer to the polarizer, thereby minimizing cracks or scratches generated during the manufacturing or processing process of the optical laminate.
[0074] The first functional coating layer 120-1 and the second functional coating layer 120-2 may each have a Vickers hardness of 18 to 41. The first functional coating layer 120-1 and the second functional coating layer 120-2 may have the same hardness, but are not limited to this, and may each have a different hardness.
[0075] The Vickers hardness may be measured using a Vickers tip of a nanoindenter (HM500, manufactured by Helmut Fischer), and may be evaluated under the conditions of a loading speed and an unloading speed of 300 mN / 20 sec, a creep time of 5 sec, and a maximum load of 100 mN. When the Vickers hardness of the functional coating layer satisfies the above range, it is possible to not only have excellent abrasion resistance, but also to further improve the bending resistance or durability of the optical laminate, and more specifically, it is possible to more effectively prevent defects such as cracks from occurring in the conductive layer due to pressure application by a spacer or chemical reactions of liquid crystal, alignment film, etc. during the bonding process of the upper laminate (first laminate) and the lower laminate (second laminate).
[0076] In one or more embodiments, the first functional coating layer 120-1 and the second functional coating layer 120-2 may each have a thickness of 1 to 30 μm, and more preferably, 1 to 20 μm. The thickness may refer to a thickness after drying, and when the thickness of the first functional coating layer 120-1 and the second functional coating layer 120-2 satisfies the above range, the layer has excellent hardness, can be thinned, and can further improve bending resistance or durability.
[0077] The protective layer serves to preserve the polarization characteristics of the polarizer from post-processing and external environments, and may be implemented in the form of a protective film.
[0078] The protective layer 130 may be formed on one or both sides of the polarizer in direct contact therewith, but is not limited thereto. For example, the protective layer may be used as a multi-layer structure in which one or more protective layers are continuously stacked, or may be formed on another member such as a retardation adjusting layer in direct contact therewith.
[0079] In one or more embodiments, the protective layer 130 may include one or more selected from the group consisting of polyethylene terephthalate (PET), polyethylene isophthalate (PEI), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), diacetyl cellulose (diacetyl cellulose), triacetyl cellulose (TAC), polycarbonate (PC), polyethylene (PE), polypropylene (PP), polymethyl acrylate (PMA), polymethyl methacrylate (PMMA), polyethyl acrylate (PEA), polyethyl methacrylate (PEMA), and cyclic olefin polymer (COP).
[0080] The retardation control layer 140 is for complementing the optical properties of the optical laminate and may be implemented in the form of a retardation film, etc., or may use a conventional or later developed retardation film, etc. For example, a quarter wave plate (1 / 4 wave plate) or a half wave plate (1 / 2 wave plate) for delaying the phase of light may be used, and these may be used alone or in combination.
[0081] The retardation control layer may be formed on one surface of the polarizer in direct contact therewith, but is not limited thereto. For example, the retardation control layer may be formed on one surface of the protective layer in direct contact therewith, or may be formed on one surface of the refractive index control layer in direct contact therewith.
[0082] The retardation adjusting layer 140 may be a polymer stretched film obtained by stretching a polymer film capable of imparting optical anisotropy by stretching in an appropriate manner, or a liquid crystal polymer film.
[0083] In one embodiment, the polymer stretched film may be a polymer layer including polyolefins such as polyethylene (PE) or polypropylene (PP), cycloolefin polymers (COP) such as polynorbornene, polyesters such as polyvinyl chloride (PVC), polyacrylonitrile (PAN), polysulfone (PSU), acrylic resins, polycarbonate (PC), and polyethylene terephthalate (PET), polyacrylate, polyvinyl alcohol (PVA), or cellulose ester polymers such as triacetyl cellulose (TAC), or a copolymer of two or more monomers among the monomers forming the polymer.
[0084] The method for obtaining the polymer stretched film is not particularly limited, and for example, the polymer material is molded into a film and then stretched. The method for forming the film is not particularly limited, and the film can be molded into a film by known methods such as injection molding, sheet molding, blow molding, injection blow molding, inflation molding, extrusion molding, foam molding, and cast molding, and secondary processing molding methods such as compressed air molding and vacuum molding may also be used. Among them, extrusion molding and cast molding are preferably used. At this time, for example, an extruder equipped with a T-die, a circular die, or the like can be used to extrude the unstretched film. When obtaining a molded product by extrusion molding, a material in which various resin components, additives, etc. are melt-kneaded in advance can be used, or the product can be molded through melt-kneading during extrusion molding. In addition, various resin components can be dissolved using a solvent common to various resin components, such as chloroform or methylene dichloride, and then cast-dried and solidified to cast-mold the unstretched film.
[0085] The polymer stretched film may be produced by uniaxially stretching the formed film in the mechanical direction (MD, lengthwise or longitudinal direction) or uniaxially stretching the formed film in the transverse direction (TD, widthwise or transverse direction) of the mechanical direction. Also, a biaxially stretched film may be produced by stretching the formed film by a sequential biaxial stretching method of roll stretching and tenter stretching, a simultaneous biaxial stretching method by tenter stretching, a biaxial stretching method by tubular stretching, or the like.
[0086] The liquid crystal polymer film may include a reactive liquid crystal compound in a polymerized state. The reactive liquid crystal compound may be the same as that of the coating type polarizer.
[0087] In one or more embodiments, the thickness of the retardation control layer may be 10 to 100 μm in the case of a polymer stretched film, and 0.1 to 5 μm in the case of a liquid crystal polymer film.
[0088] The refractive index adjustment layer 150 is provided to compensate for the refractive index difference of the optical laminate caused by the transparent conductive layer 200, and may serve to improve visibility by reducing the refractive index difference. The refractive index adjustment layer 150 may also be provided to correct a hue caused by the transparent conductive layer 200. Meanwhile, when the transparent conductive layer has a pattern, the refractive index adjustment layer can compensate for the transmittance difference between a patterned region where the pattern is formed and a non-patterned region where the pattern is not formed.
[0089] Specifically, the transparent conductive layer 200 is stacked adjacent to another member (e.g., a polarizer) having a different refractive index, and a difference in light transmittance may be induced due to the difference in refractive index between the adjacent layers. In particular, when a pattern is formed on the transparent conductive layer, a problem may occur in which the patterned region and the non-patterned region are visually distinguishable. Therefore, by including the refractive index control layer, the refractive index is compensated for, thereby reducing the difference in light transmittance of the optical laminate, and in particular, when a pattern is formed on the transparent conductive layer, the patterned region and the non-patterned region are visually distinguishable.
[0090] In one embodiment, the refractive index of the refractive index adjusting layer 150 may be appropriately selected according to the material of the adjacent member, and may be preferably 1.4 to 2.6, and more preferably 1.4 to 2.4. In this case, light loss due to a sharp difference in refractive index between the adjacent member and the transparent conductive layer 200 can be prevented.
[0091] The refractive index adjustment layer 150 is not particularly limited as long as it can prevent a sharp refractive index difference between the transparent conductive layer 200 and other components such as a polarizer, and may be formed using a compound used to form a refractive index adjustment layer conventionally or to be developed later, for example, from a refractive index adjustment layer forming composition containing a polymerizable isocyanurate compound.
[0092] In one embodiment, the polarizing plate 100 may further include other components to supplement or enhance the properties of the polarizer in addition to the above-mentioned components, for example, may further include an overcoat layer to further improve mechanical durability.
[0093] In one or more embodiments, the polarizing plate 100 may have a thickness of 30 to 200 μm, preferably 30 to 170 μm, and more preferably 50 to 150 μm, in which case the polarizing plate 100 can be used to manufacture an optical laminate having a small thickness while maintaining optical properties.
[0094] The transparent conductive layer 200 is provided for driving the liquid crystal layer 300, and may be formed in direct contact with the polarizer 100. For example, as shown in Fig. 1, the first transparent conductive layer 200-1 and the second transparent conductive layer 200-2 may be formed in direct contact with the first polarizer 100-1 and the second polarizer 100-2, respectively.
[0095] Conventional optical laminates used in the manufacture of smart windows, etc., are manufactured by forming a conductive layer for driving liquid crystal on one side of a substrate and bonding the other side of the substrate to a polarizing plate. However, the variable transmittance optical laminate according to the present invention is characterized in that it does not include a separate substrate for forming a conductive layer, but directly forms a conductive layer on one side of a polarizing plate, thereby reducing the thickness of the laminate and improving the transmittance and bending characteristics in a light transmission mode.
[0096] In one embodiment, the transparent conductive layer 200 may be formed by direct deposition on one surface of the polarizer 100. In this case, the transparent conductive layer 200 may be formed by directly contacting the pre-treated surface of the polarizer 100 after performing a pre-treatment such as a corona treatment or a plasma treatment on one surface of the polarizer 100 in order to improve adhesion to the polarizer 100. The pre-treatment is not limited to a corona treatment or a plasma treatment, and any conventional or later developed pre-treatment process may be used within the scope of the present invention.
[0097] In another embodiment, the transparent conductive layer 200 may be formed in direct contact with the polarizer 100 via an easy-adhesion layer (not shown) provided on one side of the polarizer 100 in order to improve adhesion to the polarizer 100.
[0098] The transparent conductive layer 200 preferably has a visible light transmittance of 50% or more, and may include, for example, one or more selected from the group consisting of transparent conductive oxides, metals, carbon-based materials, conductive polymers, conductive inks, and nanowires, but is not limited thereto, and any conventional or later developed transparent conductive layer material may be used.
[0099] In one or more embodiments, the transparent conductive oxide may include one or more selected from the group consisting of indium tin oxide (ITO), indium zinc oxide (IZO), indium zinc tin oxide (IZTO), aluminum zinc oxide (AZO), gallium zinc oxide (GZO), florin tin oxide (FTO), zinc oxide (ZnO), etc. The metal may include one or more selected from the group consisting of gold (Au), silver (Ag), copper (Cu), aluminum (Al), platinum (Pt), palladium (Pd), chromium (Cr), titanium (Ti), tungsten (W), niobium (Nb), tantalum (Ta), vanadium (V), iron (Fe), manganese (Mn), cobalt (Co), nickel (Ni), zinc (Zn), and alloys containing at least one of these, for example, a silver-palladium-copper (APC) alloy or a copper-calcium (CuCa) alloy. The carbon-based material may include at least one selected from the group consisting of carbon nanotubes (CNTs) and graphene, and the conductive polymer may include at least one selected from the group consisting of polypyrrole, polythiophene, polyacetylene, PEDOT, and polyaniline. The conductive ink may be an ink in which a metal powder and a curable polymer binder are mixed, and the nanowire may be, for example, a silver nanowire (AgNW).
[0100] The transparent conductive layer 200 may also be formed in a two-layer structure by combining the above materials, for example, in a two-layer structure including a metal layer and a transparent conductive oxide layer to reduce the reflectance and increase the transmittance of incident light.
[0101] The transparent conductive layer 200 may be formed by a method commonly used in the art, for example, a coating process such as spin coating, roller coating, bar coating, dip coating, gravure coating, curtain coating, die coating, spray coating, doctor coating, kneader coating, etc.; a printing process such as screen printing, spray printing, inkjet printing, relief printing, intaglio printing, and planographic printing, etc.; and a deposition process such as CVD (chemical vapor deposition), PVD (physical vapor deposition), and PECVD (plasma enhanced chemical vapor deposition), etc.
[0102] The liquid crystal layer 300 can change the driving mode of the optical stack by controlling the transmittance of light incident from one or more directions by an electric field.
[0103] The liquid crystal layer 300 may include a liquid crystal compound 310 and a ball spacer 320, and may be, for example, an area defined by a first alignment film 330-1 and a second alignment film 330-2 and a sealant 340 provided between a first polarizer 100-1 and a second polarizer 100-2.
[0104] The liquid crystal compound 310 is not particularly limited as long as it is driven by an electric field and can control the light transmittance, and any conventional or later developed liquid crystal compound can be used. For example, the contents regarding the reactive liquid crystal compound of the coating type polarizer described above can be similarly applied.
[0105] The liquid crystal behavior mode of the liquid crystal layer 300 is not particularly limited, and for example, as shown in FIG. 1, it may be driven in TN (Twisted nematic) mode, but is not limited thereto, and may also be driven in STN (Super twisted nematic) mode, VA (Vertical alignment) mode, etc.
[0106] The ball spacer 320 is not particularly limited as long as it is provided to maintain a constant liquid crystal cell gap, and preferably has a substantially spherical shape.
[0107] The ball spacer 320 preferably has a diameter of 4 to 10 μm. When the diameter of the ball spacer satisfies this range, not only can the liquid crystal cell gap be maintained at a constant level, but also there is an advantageous advantage in terms of thinning the liquid crystal layer.
[0108] In addition, when viewed from a planar direction, the area of the ball spacer 320 in the liquid crystal layer 300 is preferably 0.01 to 10%. When the occupancy rate of the ball spacer satisfies the above range, it is advantageous in terms of improving the user's visibility and the transmittance in the light transmission mode.
[0109] The ball spacers 320 are preferably included in the liquid crystal layer 300 in an appropriate number according to the diameter of the ball spacer. In one embodiment, the ball spacer has a diameter (d; μm) per unit area (1 mm 2 The number of ball spacers (A) per ball may satisfy the following formula 1: [Formula 1] -1.3333d 3 +32.321d 2 -265.2d+802.14≦A≦-17.639d3 +427.26d 2 -3502.2d+10736
[0110] For example, if the diameter (d) of the ball spacer is 4 μm, the ball spacer has a unit area (1 mm 2 The number (A) of ball spacers having a diameter of 4 μm per one ball is 173.1448{=-1.3333(4) 3 +32.321(4) 2 -265.2(4)+802.14} to 2434.464{=-17.639(4)} 3 +427.26(4) 2 -3502.2(4)+10736}, and when the diameter (d) of the ball spacer is 10 μm, the unit area (1 mm 2 The number (A) of ball spacers having a diameter of 10 μm per unit area is 48.94{=-1.3333(10) 3 +32.321(10) 2 -265.2(10)+802.14} to 801{=-17.639(10) 3 +427.26(10) 2 -3502.2(10)+10736} may also be used.
[0111] The diameter of the ball spacer is not particularly limited in the measurement area when the ball spacer is substantially spherical, but when the ball spacer is not perfectly spherical, it may mean the major axis side of a circle or ellipse formed by the ball spacer when the ball spacer is viewed from a planar direction.
[0112] Unit area (1mm 2When the number (A) of ball spacers per unit area (1 mm2) satisfies the relationship of the above formula 1, it is advantageous in that the liquid crystal cell gap can be kept constant without causing defects in the appearance of the liquid crystal. 2 If the number (A) of ball spacers per unit area (1 mm2) is less than the lower limit of the formula 1, the liquid crystal cell gap in a portion of the liquid crystal layer may decrease, causing the portion to be visually recognized by the user as black amorphous unevenness (see FIG. 7), and a short circuit may occur between the first transparent conductive layer and the second transparent conductive layer, preventing smooth operation of the optical laminate. 2 If the number (A) of ball spacers per unit area exceeds the upper limit of the formula 1, the ball spacers themselves may reduce the transmittance in the light transmission mode, causing haze, and may also form clusters between the ball spacers, and the clustered areas may be visually recognized by the user as white dot-shaped irregularities (see FIG. 8).
[0113] In a more preferred embodiment of the present invention, the ball spacer has a diameter (d; μm) per unit area (1 mm 2 The number of ball spacers (A) per i) When 4≦d<4.5, A is 184 to 2,420, ii) 4.5≦d<5.5, A is 118 to 1,550, iii) 5.5≦d<6.5, A is 98 to 1,290, iv) When 6.5≦d<7.5, A is 84 to 1,105; v) When 7.5≦d<8.5, A is 74 to 970; vi) When 8.5≦d<9.5, A is 65 to 860; vii) When 9.5≦d≦10, A may satisfy the relationship of 59 to 775. In this case, it can be said that there is a further advantage in terms of suppressing occurrence of defects in the appearance of the liquid crystal and maintaining the liquid crystal cell gap.
[0114] In another embodiment of the present invention, the ball spacer has a diameter (d; μm) per unit area (1 mm 2 The number of ball spacers per ball spacer (A) and the Vickers hardness (B) of the functional coating layer are i) When 4≦d<4.5, A×B 2 60,000 to 1,650,000, ii) When 4.5≦d<5.5, A×B 2 40,000 to 1,050,000, iii) When 5.5≦d<6.5, A×B 2 31,000 to 900,000, iv) 6.5≦d<7.5, A×B 2 27,000 to 800,000, v) When 7.5≦d<8.5, A×B 2 24,000 to 700,000, vi) When 8.5≦d<9.5, A×B 2 21,000 to 600,000, vii) When 9.5≦d≦10, A×B 2 may satisfy the relationship between 19,000 and 550,000.
[0115] As described above, the Vickers hardness value of the functional coating layer is 18 to 41, and when the Vickers hardness value is small, the corresponding part is relatively soft, and when the Vickers hardness value is large, the corresponding part is relatively hard. However, even if the Vickers hardness value is set as above, the magnitude of the stress applied to one ball spacer varies depending on the number of ball spacers per unit area, and if the appropriate number of ball spacers (A) according to the diameter of the ball spacers is not set, the stress concentration applied to each ball spacer increases, increasing the possibility of cracks occurring.
[0116] Therefore, the diameter (d; μm) of the ball spacer is expressed as the unit area (1 mm 2 When the number of ball spacers (A) per cell and the Vickers hardness (B) of the functional coating layer satisfy the above ranges, it is advantageous not only in terms of suppressing the occurrence of defects in the appearance of the liquid crystal and maintaining the liquid crystal cell gap, but also in terms of preventing the occurrence of cracks.
[0117] As described above, the Vickers Hardness (B) value of the functional coating layer may be any value when the Vickers hardness values of the first functional coating layer and the second functional coating layer are substantially equal, and when the Vickers hardness values of the first functional coating layer and the second functional coating layer are different, it may mean the smaller value of the two.
[0118] In another embodiment of the present invention, the liquid crystal layer may further include other types of spacers, such as column spacers, in addition to the ball spacers, if necessary.
[0119] The alignment film 330 is not particularly limited as long as it can impart alignment to the liquid crystal compound, and may preferably include a photoalignable or photocurable polymer, etc. For example, the alignment film 330 may be manufactured by applying and curing an alignment film coating composition including a photoalignable or photocurable polymer, a photopolymerization initiator, and a solvent.
[0120] The photo-alignable or photo-curable polymer is not particularly limited, and may be a cinnamate-based polymer, a polyimide-based polymer, or the like, such as poly(vinyl cinnamate) (PVCi), poly(siloxane cinnamate) (PSCN), poly(ω(4-chalconyloxy)alkoxyphenylmaleimide, 6-FDA-HAB-Cl, or a conventional or later developed polymer capable of exhibiting alignment.
[0121] The alignment film 330 may include an adhesion layer formed at the contact interface with the ball spacer 320 .
[0122] In one or more embodiments, the stickiness imparting layer 350 may be in the form of a first stickiness imparting layer 350-1 formed at the contact interface between a first alignment film 330-1 and a ball spacer 320 as shown in FIG. 2a, a second stickiness imparting layer 350-2 formed at the contact interface between a second alignment film 330-2 and a ball spacer 320 as shown in FIG. 2b, and / or a first stickiness imparting layer 350-1 and a second stickiness imparting layer 350-2 formed at the contact interfaces between the first alignment film 330-1, the second alignment film 330-2, and the ball spacer 320, respectively, as shown in FIG. 2c.
[0123] The adhesion imparting layer 350 may be formed by applying a predetermined heat to the ball spacer 320 and melting the thermal inverse stratification (alkyl chain) present on the surface of the ball spacer 320 toward the alignment layer 330, and may be manufactured by, for example, spraying a mixed solvent containing the ball spacer under a predetermined temperature condition, and at this time, the heating may be performed under a temperature condition of preferably 60 to 150° C., and more preferably, under a temperature condition of 80 to 120° C. Therefore, the adhesion imparting layer may be formed integrally with the ball spacer.
[0124] In this manner, the ball spacer 320 is provided via the adhesion imparting layer 350 formed on the first alignment film 330-1 and the second alignment film 330-2, so that the reliability of the spacer can be further improved.
[0125] The sealant 340 may include a curable resin as a base resin. The base resin may be a UV-curable resin or a thermosetting resin known in the art for use in sealants. The UV-curable resin may be a polymer of a UV-curable monomer. The thermosetting resin may be a polymer of a thermosetting monomer.
[0126] The base resin of the sealant 340 may be, for example, an acrylate-based resin, an epoxy-based resin, a urethane-based resin, a phenol-based resin, or a mixture of the above resins. In one embodiment, the base resin may be an acrylate-based resin, and the acrylate-based resin may be a polymer of an acrylic monomer. The acrylic monomer may be, for example, a multifunctional acrylate. In another embodiment, the sealant may further include a monomer component in the base resin. The monomer component may be, for example, a monofunctional acrylate. In this specification, a monofunctional acrylate may mean a compound having one acrylic group, and a multifunctional acrylate may mean a compound having two or more acrylic groups. The curable resin may be cured by irradiation with ultraviolet light and / or heating. The ultraviolet irradiation conditions or heating conditions may be appropriately performed within a range that does not impair the object of the present application. The sealant may further include an initiator, for example, a photoinitiator or a thermal initiator, if necessary.
[0127] The sealant 340 may be formed by a method commonly used in the art, for example, by drawing the sealant onto the outer periphery (i.e., non-active area) of the liquid crystal layer using a dispenser equipped with a nozzle.
[0128] The variable transmittance optical laminate of the present invention may further include other components within the scope of the present invention, for example, it may further include a tacky adhesive layer 400, preferably an adhesive layer, on one side (see FIG. 4) or both sides (not shown) of the optical laminate, or it may further include an ultraviolet absorbing layer, etc.
[0129] The adhesive layer 400 may be formed using an adhesive or pressure-sensitive adhesive, and preferably has an appropriate adhesive strength so as to prevent peeling, air bubbles, etc. from occurring when the optical laminate is handled, as well as transparency and thermal stability.
[0130] The adhesive may be any conventional or later developed adhesive, for example a light curable adhesive.
[0131] The photocurable adhesive exhibits strong adhesive strength by being crosslinked and cured when exposed to active energy rays such as ultraviolet (UV) rays and electron beams (EB), and may be composed of reactive oligomers, reactive monomers, photopolymerization initiators, etc.
[0132] The reactive oligomer is an important component that determines the properties of the adhesive, and forms a polymer bond by photopolymerization to form a hardened coating. Usable reactive oligomers include polyester resins, polyether resins, polyurethane resins, epoxy resins, polyacrylic resins, silicone resins, etc.
[0133] The reactive monomer functions as a crosslinking agent and a diluent for the reactive oligomer, and affects the adhesive properties. Usable reactive monomers include monofunctional monomers, polyfunctional monomers, epoxy monomers, vinyl ethers, cyclic ethers, and the like.
[0134] The photopolymerization initiator absorbs light energy to generate radicals or cations to initiate photopolymerization, and may be selected from those suitable for the photopolymerizable resin.
[0135] The adhesive may be a conventional or later developed adhesive, and in one or more embodiments, may be an acrylic adhesive, a rubber adhesive, a silicone adhesive, a urethane adhesive, a polyvinyl alcohol adhesive, a polyvinylpyrrolidone adhesive, a polyacrylamide adhesive, a cellulose adhesive, a vinyl alkyl ether adhesive, etc. The adhesive is not particularly limited as long as it has adhesive strength and viscoelasticity, but in terms of availability, etc., it may be preferably an acrylic adhesive, and may contain, for example, a (meth)acrylate copolymer, a crosslinking agent, and a solvent.
[0136] The crosslinking agent may be a conventional or later developed crosslinking agent, and may include, for example, a polyisocyanate compound, an epoxy resin, a melamine resin, a urea resin, a dialdehyde, a methylol polymer, or the like, and preferably includes a polyisocyanate compound.
[0137] The solvent may include a typical solvent used in the field of resin compositions, such as alcohol-based compounds such as methanol, ethanol, isopropanol, butanol, and propylene glycol methoxy alcohol; ketone-based compounds such as methyl ethyl ketone, methyl butyl ketone, methyl isobutyl ketone, diethyl ketone, and dipropyl ketone; acetate-based compounds such as methyl acetate, ethyl acetate, butyl acetate, and propylene glycol methoxy acetate; cellosolve-based compounds such as methyl cellosolve, ethyl cellosolve, and propyl cellosolve; and hydrocarbon-based compounds such as hexane, heptane, benzene, toluene, and xylene. These may be used alone or in combination of two or more.
[0138] The thickness of the adhesive layer 400 may be appropriately determined depending on the type of resin acting as an adhesive, adhesive strength, the environment in which the adhesive is used, etc. In one embodiment, the adhesive layer may have a thickness of 0.1 to 500 μm, preferably 0.5 to 450 μm, and more preferably 1 to 400 μm, in order to ensure sufficient adhesive strength and minimize the thickness of the optical laminate.
[0139] In one embodiment, the adhesive layer 400 may be formed on one or both sides of the polarizing plate by a lamination method.
[0140] The ultraviolet absorbing layer is not particularly limited as long as it is used to prevent deterioration of the optical laminate due to ultraviolet rays. For example, it may be a salicylic acid-based ultraviolet absorber (phenyl salicylate, p-tert-butyl salicylate, etc.), a benzophenone-based ultraviolet absorber (2,4-dihydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, etc.), a benzotriazole-based ultraviolet absorber (2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-t 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(3'',4'',5'',6''-tetrahydrophthalimidomethyl)-5'-methylphenyl)benzotriazole, 2,2-methylenebis(4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazo 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-(2-octyloxycarbonylethyl)-phenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(1-methyl-1-phenylethyl)-5'-(1,1,3,3-tetramethylbutyl)-phenyl)benzotriazole, 2-(2H-benzotriazol-2-yl)-6-(linear and side chain dodecyl)-4-methylphenol, a mixture of octyl-3-[3-tert-butyl-4-hydroxy-5-(chloro-2H-benzotriazol-2-yl)phenyl]propionate and 2-ethylhexyl-3-[3-tert-butyl-4-hydroxy-5-(5-chloro-2H-benzotriazol-2-yl)phenyl]propionate, etc.), cyanoacrylate-based ultraviolet absorbers (2'-ethylhexyl-2-cyano-3,3-diphenylacrylate, ethyl-2-cyano-3-(3',4'-methylenedioxyphenyl)-acrylate, triazine-based ultraviolet absorbers, etc. may be used, and benzotriazole-based ultraviolet absorbers and triazine-based ultraviolet absorbers, which are highly transparent and have an excellent effect of preventing deterioration of the polarizing plate and the transmittance variable layer, are preferred, and benzotriazole-based ultraviolet absorbers with a more suitable spectral absorption spectrum are particularly preferred. The benzotriazole-based ultraviolet absorbers may be bis(Bis)-modified, for example, 6,6'-methylenebis(2-(2H-benzo[d][1,2,3]triazol-2-yl)-4-(2,4,4-trimethylpentan-2-yl)phenol), 6,6'-methylenebis(2-(2H-benzo[d][1,2,3]triazol-2-yl)-4-(2-hydroxyethyl)phenol), etc.,
[0141] The present invention includes the variable transmittance optical laminate, as well as a smart window including the same. The present invention also includes a means of transportation including the smart window, for example, an automobile to which the smart window is applied to at least one of a front window, a rear window, a side window, a sunroof window, and an interior partition, a wearable device including the smart window, and a building fixture.
[0142] For example, an automobile including the smart window of the present invention may be manufactured by bonding car glass 500 onto both sides of an optical laminate including a polarizing plate 100, a transparent conductive layer 200, a liquid crystal layer 300, and a tacky adhesive layer 400 (see FIG. 5), for example, by placing an adhesive film and car glass on both sides of the optical laminate, and then heating the laminate at a temperature of 90° C. and a vacuum of about 1 bar for 10 to 20 minutes using a press machine, and the adhesive film may include an EVA film, a PVB film, etc.
[0143] In addition, the optical laminate may have a building fixture (glass for fixtures) 600 bonded to one side (see FIG. 6a) or both sides (see FIG. 6b) of it, or the optical laminate may have glass for fixtures bonded to one side thereof by a lamination method to produce a smart window product for fixtures having the same configuration as that shown in FIG. 6a, or the optical laminate may have glass for fixtures bonded to both sides thereof by applying a UV adhesive and then curing with UV to produce a smart window product for fixtures having the same configuration as that shown in 6b. EXAMPLES
[0144] Hereinafter, the present invention will be described in detail with reference to the embodiments. However, the present invention is not limited to the embodiments disclosed below, and may be embodied in various different forms. However, the embodiments are provided to fully disclose the present invention and to fully inform those skilled in the art of the present invention of the scope of the invention, and the present invention is defined only by the scope of the claims.
[0145] Manufacturing example 1: Production of polarizing plates (1) Swelling treatment process A 60 μm thick polyvinyl alcohol film (raw film) (manufactured by Kuraray Co., Ltd., product name "Kuraray Poval Film VF-PE#6000", average polymerization degree 2400, saponification degree 99.9 mol%) was continuously unwound from a raw roll and transported, and immersed in a swelling bath containing pure water at 20°C for 30 seconds. In this swelling process, inter-roll stretching (longitudinal uniaxial stretching) was performed with a difference in peripheral speed between the nip rolls. The stretching ratio based on the raw film was 2.5 times.
[0146] (2) Dyeing process Next, the film that had passed through the nip rolls was immersed in a dye bath at 30° C. with a mass ratio of pure water / potassium iodide / iodine / boric acid of 100 / 2 / 0.01 / 0.3 for 120 seconds. In this dyeing treatment, roll-to-roll stretching (longitudinal uniaxial stretching) was also performed with a difference in peripheral speed between the nip rolls. The stretching ratio was 1.1 times based on the film after the swelling treatment step.
[0147] (3) Crosslinking process Next, the film that had passed through the nip roll was immersed in a first crosslinking bath at 56° C., in which the mass ratio of pure water / potassium iodide / boric acid was 100 / 12 / 4, for 70 seconds. Roll-to-roll stretching (longitudinal uniaxial stretching) was performed with a difference in peripheral speed between the nip roll and a nip roll provided between the first crosslinking bath and the second crosslinking bath. The stretching ratio was 1.9 times based on the film after the dyeing process.
[0148] (4) Complementary color processing process Next, the film after the crosslinking treatment was immersed for 10 seconds in a second crosslinking bath at 40° C. containing potassium iodide / boric acid / pure water (mass ratio) of 9 / 2.9 / 100.
[0149] (5) Cleaning process Next, the film after the second crosslinking treatment was immersed in a cleaning bath containing pure water at 14°C for 5 seconds, and the shower volume was 5 m 3 / h and shower temperature 14°C.
[0150] (6) Drying process Next, the film after the washing process was passed through a drying oven and heated and dried at 80°C for 190 seconds to produce a polarizer film. The moisture content after drying was 13.6%, and the thickness of the obtained polarizer film was about 21 μm.
[0151] (7) Bonding process Next, a water-based adhesive containing 5 parts by weight of polyvinyl alcohol per 100 parts by weight of water was prepared as an adhesive. Then, protective films were laminated on both sides of the polarizer film using the prepared UV adhesive. The obtained laminate was exposed to UV light to harden the adhesive, and an upper polarizing plate and a lower polarizing plate were produced. The thickness of the adhesive layer in the obtained polarizing plate was about 2 μm.
[0152] Production Example 2: Production of composition for forming hard coating layer A composition for forming a hard coating layer was prepared by mixing 16.2 g of a dendrimer compound (Miwan Specialty Chemical, SP-1106), 14.4 g of inorganic nanoparticles (10 to 20 nm, silica particles: 50 wt %, solvent: methyl ethyl ketone (MEK)), 1.8 g of a multifunctional (meth)acrylate compound containing an ethylene glycol group, 0.7 g of a photoinitiator (1-hydroxycyclohexyl phenyl ketone), and 2.9 g of methyl ethyl ketone.
[0153] Manufacturing Example 3: Production of hard coating layer The composition for forming the hard coating layer prepared in Preparation Example 2 was applied to one side of each of the upper and lower polarizing plates prepared in Preparation Example 1, adjusted in type and solid content of Mayer Bar, cured, and then bar-coated with a calculated hard coating thickness. The hard coating was then dried at 80° C. for 5 minutes and then exposed to a high-pressure mercury lamp at 500 mJ / m 2 The upper and lower polarizing plates were each formed with a hard coating layer on one surface by curing with an amount of light of 1000 nm.
[0154] Manufacturing Example 4: Fabrication of transparent conductive layer The upper and lower polarizing plates prepared in Preparation Example 3 were inserted, 450W DC power was applied to operate the sputtering gun, and plasma was then induced to the ITO (10wt% Sn doped In2O3) target to form a transparent conductive film (90nm). The formed transparent conductive film was ion-treated by operating an ion gun with 50W DC power. At this time, the pressure was maintained at 3mTorr at room temperature, and argon gas and oxygen gas were supplied at 30sccm and 1sccm, respectively. At this time, the ITO thickness was measured using FT-SEM, and the ITO sheet resistance (Ω / □) was measured using a four point probe.
[0155] Manufacturing Example 5: Fabrication of Alignment Film An alignment liquid was coated on the ITO surfaces of the upper and lower polarizers prepared in Preparation Example 4 and dried (80° C. / 2 min.) Then, UV was irradiated onto the dried alignment liquid to prepare an alignment film.
[0156] Manufacturing Example 6: Spacer Scattering Manufacturing First, a mixed solvent was prepared by mixing ball spacers (manufactured by SEKISUI) with 100 ml of IPA. Thereafter, the conductive layer laminate of the lower polarizer of Preparation Example 5 was placed in a spacer sprayer (SDSS-KHU02, SHINDO ENG LAB), and the mixed solvent prepared above was sprayed at 110°C and then dried for 20 minutes to form ball spacers on the alignment film of the lower polarizer, in which the thermal inverse stratification on the spacer particle surface was partially melted and fixed. Thereafter, the area of the spacer per unit area (1 mm2) was measured using an optical microscope. 2 The number of ball spacers present in the
[0157] Manufacturing Example 7: Production of optical laminate A sealant (UVF-006, 70,000 mPa s, Sekisui) was applied to the outer periphery of the lower polarizer manufactured in Manufacturing Example 6 using a sealant dispenser (SHOT mini 200Ωx, Musashi) according to the product size. Then, with the polarization axes of the upper and lower polarizers parallel to each other at 0° or 90°, liquid crystal was injected onto the alignment film of the upper polarizer using the ODF process. Then, the upper and lower polarizers were placed in a vacuum of 1.5 kg / cm. 2 After bonding with pressure, UV curing (500 mJ / cm) was performed along the sealant line. 2 ) was carried out to produce an optical laminate for smart windows.
[0158] Examples and Comparative Examples Diameter of ball spacer, unit area (1 mm 2 Except for the number of ball spacers per ball (A) and the thickness and hardness (B) of the hard coating layer as shown in Tables 1 and 2 below, optical laminates of Examples 1 to 49 and Comparative Examples 1 to 22 were prepared by the above Preparation Examples 1 to 7, respectively, and are shown in Tables 1 and 2 below.
[0159] In addition, the optical laminates produced in Preparation Examples 1 to 7 were heat-treated at 110° C. for 20 minutes to produce an optical laminate of Example 50, which is shown in Table 1 below.
[0160] In addition, an optical laminate of Comparative Example 23 in which the upper polarizing plate and the lower polarizing plate did not include a hard coating layer was prepared by the same method as Preparation Examples 1 and 4 to 7, and the results are shown in Table 2 below.
[0161] [Table 1-1]
[0162] [Table 1-2]
[0163] [Table 2]
[0164] Experimental Example (1) Evaluation of hard coating layer thickness For the optical laminates of Examples 1 to 50 and Comparative Examples 1 to 23, the thickness of the polarizing plate before and after the formation of the hard coating layer was measured using a thickness meter (MH-15M, manufactured by SENDAI NIKON Co., Ltd.), and the thickness of the hard coating layer was calculated and shown in Tables 1 and 2 above.
[0165] (2) Evaluation of pencil hardness For the optical laminates of Examples 1 to 50 and Comparative Examples 1 to 23, the pencil hardness of the hard coating layer surface was measured using a pencil hardness tester (manufactured by SUKBO Science Co., Ltd., Korea). The results are shown in Tables 1 and 2 above.
[0166] Specifically, a polarizing plate was attached to a 80×60 mm glass plate using an adhesive, and then a pencil (manufactured by Mitsubishi Corp.) was placed on the hard-coated surface at a 45° angle, and a 750 g weight was applied to scratch the surface at a speed of 300 mm / min, five times per pencil hardness, and the surface was heat-treated at 100° C. for 10 minutes to determine whether scratches were generated.
[0167] (3) Vickers hardness measurement The Vickers hardness of the optical laminates of Examples 1 to 50 and Comparative Examples 1 to 23 was measured using a Vickers tip of a nanoindenter (HM500, manufactured by Helmut Fischer), and is shown in the above Tables 1 and 2. At this time, the loading and unloading speeds were similarly 300 mN / 20 sec, the creep time was maintained at 5 sec, and the maximum load was 100 mN.
[0168] (4) Liquid crystal appearance evaluation (1) - Evaluation of the occurrence of black amorphous unevenness The optical laminates of Examples 1 to 50 and Comparative Examples 1 to 23 were visually evaluated for the presence or absence of black amorphous unevenness as in the case of FIG. 7, and the results are shown in Tables 3 and 4 below. <Evaluation criteria> Good: No black amorphous spots Defective: Black amorphous spots occur
[0169] (5) Liquid crystal appearance evaluation (2) - Evaluation of the occurrence of white dot-shaped irregularities The optical laminates of Examples 1 to 50 and Comparative Examples 1 to 23 were visually evaluated for the occurrence of white dot-shaped unevenness as in the case of FIG. 8, and the results are shown in Tables 3 and 4 below. <Evaluation criteria> Good: No white dot irregularities Defective: White dots appear
[0170] (6) Evaluation of reliability mandrels In order to evaluate the bending properties and cracking tendency of the optical laminates of Examples 1 to 50 and Comparative Examples 1 to 23 using a cylindrical bending tester (Lab-Q D605, manufactured by CKSI), sample specimens of the Examples and Comparative Examples, each measuring 100 x 100 mm, were placed so that the lower polarizing plate was in contact with an iron bar with a diameter of 4 mm, and a load of 1 kg was applied to the outside of the folded portion in a folded state. The sample was then placed in an oven at 90°C for 2 hours, and then placed at room temperature. The folded area was observed to evaluate the occurrence of cracks, and the results are shown in Tables 3 and 4 below. <Evaluation criteria> Good: No change in appearance or cracks Defect: Change in appearance or cracks occur
[0171] [Table 3-1]
[0172] [Table 3-2]
[0173] [Table 4]
[0174] Referring to Tables 1 to 4 above, the Vickers hardness (B) of the hard coating layer (functional coating layer) is 18 to 41, When the ball spacer diameter is 4 μm, the unit area (1 mm 2 ) the number of ball spacers (A) per 3 +32.321(4) 2 -265.2(4)+802.14} to 2434.464{=-17.639(4)} 3 +427.26(4) 2 -3502.2(4)+10736}; When the ball spacer diameter is 5 μm, the unit area (1 mm 2 ) the number of ball spacers (A) per 3 +32.321(5) 2 -265.2(5)+802.14} to 1701.625{=-17.639(5)} 3 +427.26(5) 2 -3502.2(5)+10736}; Examples 8 to 14; When the ball spacer diameter is 6 μm, the unit area (1 mm 2 ) the number of ball spacers (A) per 3 +32.321(6) 2 -265.2(6)+802.14} to 1294.136{=-17.639(6)} 3 +427.26(6) 2 -3502.2(6)+10736}; Examples 15 to 21 and 50; When the ball spacer diameter is 7 μm, the unit area (1 mm 2 ) The number of ball spacers (A) per 3 +32.321(7) 2 -265.2(7)+802.14} to 1106.163{=-17.639(7)} 3 +427.26(7) 2 -3502.2(7)+10736}; Examples 22 to 28; When the ball spacer diameter is 8 μm, the unit area (1 mm 2 ) the number of ball spacers (A) per 3 +32.321(8) 2 -265.2(8)+802.14} to 1031.872{=-17.639(8)} 3 +427.26(8) 2 -3502.2(8)+10736}; Examples 29 to 35; When the ball spacer diameter is 9 μm, the unit area (1 mm 2) the number of ball spacers (A) per 3 +32.321(9) 2 -265.2(9)+802.14} to 965.429{=-17.639(9)} 3 +427.26(9) 2 -3502.2(9)+10736}; and When the ball spacer diameter is 10 μm, the unit area (1 mm 2 ) the number of ball spacers (A) per 3 +32.321(10) 2 -265.2(10)+802.14} to 801{=-17.639(10) 3 +427.26(10) 2 The optical laminates of Examples 43 to 49, which satisfied the above formula {-3502.2(10)+10736}, not only did they not have black amorphous unevenness and white dot-shaped unevenness, but also, as a result of evaluation using a reliability mandrel, it was found that no change in shape or cracks occurred.
[0175] In response to this, When the ball spacer diameter is 4 μm, the unit area (1 mm 2 Comparative Example 1 in which the number of ball spacers per ball (A) is 145; When the ball spacer diameter is 5 μm, the unit area (1 mm 2 Comparative Example 3 in which the number of ball spacers per ball (A) is 93; When the ball spacer diameter is 6 μm, the unit area (1 mm 2 Comparative Example 5, in which the number of ball spacers per ball (A) is 77; When the ball spacer diameter is 7 μm, the unit area (1 mm 2 Comparative Example 7 in which the number of ball spacers per ball (A) is 66; When the ball spacer diameter is 8 μm, the unit area (1 mm 2 Comparative Example 9 in which the number of ball spacers per ball (A) is 58; When the ball spacer diameter is 9 μm, the unit area (1 mm 2 Comparative Example 11 in which the number of ball spacers per ball (A) is 52; and When the ball spacer diameter is 10 μm, the unit area (1 mm 2 As in the optical laminate of Comparative Example 13 in which the number (A) of ball spacers per unit area (1 mm 2 It was found that when the number (A) of ball spacers per unit area was less than the lower limit of the formula 1 of the present invention, black amorphous unevenness occurred in the area where there were not enough ball spacers, resulting in poor appearance of the liquid crystal.
[0176] Also, When the ball spacer diameter is 4 μm, the unit area (1 mm 2 Comparative Example 2 in which the number of ball spacers per ball (A) is 2468; When the ball spacer diameter is 5 μm, the unit area (1 mm 2 Comparative Example 4 in which the number of ball spacers per ball (A) is 1720; When the ball spacer diameter is 6 μm, the unit area (1 mm 2 Comparative Example 6, in which the number of ball spacers per ball (A) is 1316; When the ball spacer diameter is 7 μm, the unit area (1 mm 2 Comparative Example 8, in which the number of ball spacers per ball (A) is 1,127; When the ball spacer diameter is 8 μm, the unit area (1 mm 2 Comparative Example 10 in which the number of ball spacers per ball (A) is 1050; When the ball spacer diameter is 9 μm, the unit area (1 mm 2 Comparative Example 12 in which the number of ball spacers per ball (A) is 980; and When the ball spacer diameter is 10 μm, the unit area (1 mm 2 As in the optical laminate of Comparative Example 14, in which the number (A) of ball spacers per unit area (1 mm 2It has been found that when the number (A) of ball spacers per pixel exceeds the upper limit of the formula 1 of the present invention, white dot-shaped irregularities occur due to crowding between the ball spacers, resulting in poor appearance of the liquid crystal.
[0177] Also, The optical laminates of Comparative Examples 15 to 23, which did not include a hard coating layer (functional coating layer) or had a hard coating layer (functional coating layer) with a Vickers hardness (B) of 17 or 44, outside the range of 18 to 41, were found to have changes in shape or cracks as a result of evaluation using a reliability mandrel.
[0178] Therefore, when two different polarizing plates included in an optical laminate each include a functional coating layer, the Vickers hardness of the functional coating layer is 18 to 41, and the number of ball spacers per unit area relative to the diameter of the ball spacer satisfies Equation 1, it can be seen that not only is the wear resistance, bending resistance, and durability improved, but also the occurrence of defects in the appearance of the liquid crystal is suppressed. [Industrial Applicability]
[0179] According to the variable transmittance optical laminate of the present invention, the process of forming a conductive layer on a substrate and then bonding it to other components required for forming a conventional optical laminate can be omitted, and the manufacturing process can be simplified compared to the conventional optical laminate.
Claims
1. a first laminate including a first polarizing plate including a first functional coating layer, a first transparent conductive layer, and a first alignment film laminated in this order; a second laminate facing the first laminate, the second laminate including a second polarizing plate including a second functional coating layer, a second transparent conductive layer, and a second alignment film laminated in this order; a liquid crystal layer disposed between the first stack and the second stack; The liquid crystal layer includes a ball spacer provided via an adhesion imparting layer formed on at least one of a first alignment film and a second alignment film, The ball spacer has a diameter of 4 to 10 μm; At least one of the first transparent conductive layer and the second transparent conductive layer is formed in direct contact with one of the first polarizing plate and the second polarizing plate, The first functional coating layer and the second functional coating layer each have a Vickers Hardness of 18 to 41; The ball spacer diameter (d; μm) and unit area (1 mm 2 The number (A) of ball spacers per ball spacer satisfies the following formula 1: [Formula 1] <h2 style=";text-align:left;direction:ltr">15333333d<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> 23222215<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> 2656 ...<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> 24262222<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> 3352 ...
2. The ball spacer diameter (d; μm) and unit area (1 mm 2 The number of ball spacers (A) per i) When 4≦d<4.5, A is from 184 to 2,420; ii) 4.5≦d<5.5, A is 118 to 1,550; iii) when 5.5≦d<6.5, A is from 98 to 1,290; iv) 6.5≦d<7.5, A is from 84 to 1,105; v) When 7.5≦d<8.5, A is from 74 to 970; vi) when 8.5≦d<9.5, A is 65 to 860; vii) When 9.5≦d≦10, A satisfies the relationship of 59 to 775. The variable transmittance optical laminate according to claim 1 .
3. The ball spacer diameter (d; μm) and unit area (1 mm 2 The number of ball spacers (A) per ball and the Vickers Hardness (B) of the functional coating layer are i) When 4≦d<4.5, A×B 2 60,000 to 1,650,000, ii) When 4.5≦d<5.5, A×B 2 40,000 to 1,050,000, iii) When 5.5≦d<6.5, A×B 2 31,000 to 900,000, iv) When 6.5≦d<7.5, A×B 2 27,000 to 800,000, v) When 7.5≦d<8.5, A×B 2 24,000 to 700,000, vi) When 8.5≦d<9.5, A×B 2 21,000 to 600,000, vii) A × B when 9.5 ≦ d ≦ 10 2 The variable transmittance optical laminate according to claim 1 , wherein the relationship is from 19,000 to 550,000.
4. The variable transmittance optical laminate according to claim 1 , wherein the adhesion imparting layer is integrally formed with a ball spacer.
5. 2. The variable transmittance optical laminate according to claim 1, wherein the area of the ball spacer in the liquid crystal layer is 0.01% to 10% of the area of the liquid crystal layer.
6. The variable transmittance optical laminate according to claim 1 , wherein the first functional coating layer and the second functional coating layer each include at least one of a hard coating layer and a low refractive index layer.
7. The low refractive index layer is made of SiO 2 , Al 2 O 3 , MgF 2 , CaF 2 7. The variable transmittance optical stack according to claim 6, comprising at least one selected from the group consisting of: and cryolite.
8. 2. The variable transmittance optical laminate of claim 1, wherein at least one of the first transparent conductive layer and the second transparent conductive layer is formed in direct contact with one of the first polarizer and the second polarizer without a separate substrate between the transparent conductive layer and the first polarizer and the second polarizer.
9. The variable transmittance optical laminate of claim 1 , wherein at least one of the first transparent conductive layer and the second transparent conductive layer includes an easy-adhesion layer between the first polarizing plate and the second polarizing plate and is formed in direct contact with the first polarizing plate and the second polarizing plate.
10. 2. The variable transmittance optical laminate of claim 1, wherein at least one of the first transparent conductive layer and the second transparent conductive layer comprises at least one selected from the group consisting of transparent conductive oxides, metals, carbon-based materials, conductive polymers, conductive inks, and nanowires.
11. 2. The variable transmittance optical laminate according to claim 1, wherein at least one of the first polarizing plate and the second polarizing plate further comprises at least one selected from the group consisting of a protective layer, a phase difference control layer, and a refractive index control layer.
12. The variable transmittance optical laminate according to claim 1 , wherein at least one of the first polarizing plate and the second polarizing plate has a thickness of 30 to 200 μm.
13. The variable transmittance optical laminate according to claim 1 , further comprising at least one layer selected from the group consisting of an overcoat layer, an adhesive layer, and an ultraviolet absorbing layer.
14. A method for producing the variable transmittance optical laminate according to any one of claims 1 to 13.
15. A smart window comprising the variable transmittance optical laminate of any one of claims 1 to 13.
16. A means of transportation comprising the smart window of claim 15.
17. 16. A car comprising the smart window according to claim 15, applied to at least one of a front window, a rear window, a side window, a sunroof window, and an interior partition.
18. A wearable device comprising the smart window of claim 15.
19. Architectural fittings comprising the smart window of claim 15.